2022
DOI: 10.3390/biomedicines10040794
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Amplification Is a Phenomenon of IDH Wildtype and TERT Mutated High-Grade Glioma: An Integrated Analysis Using Fluorescence In Situ Hybridization and DNA Methylome Profiling

Abstract: Gliomas are the most common intrinsic brain tumors in adults, and in accordance with their clinical behavior and patients’ outcome, they are graded by the World Health Organization (WHO) classification of brain tumors. One very interesting candidate for targeted tumor therapy may be epidermal growth factor receptor (EGFR) amplification. Here, we performed an integrated comparative analysis of EGFR amplification in 34 glioma samples using standard fluorescence in situ hybridization (FISH) and Illumina EPIC Infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Molecular genetic analyses for IDH1 , IDH2 mutations, as well as DNA methylation were performed as previously described [ 26 , 27 , 28 ]. In brief, representative tumor regions were microscopically identified and dissected.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Molecular genetic analyses for IDH1 , IDH2 mutations, as well as DNA methylation were performed as previously described [ 26 , 27 , 28 ]. In brief, representative tumor regions were microscopically identified and dissected.…”
Section: Methodsmentioning
confidence: 99%
“…Mutational analysis of IDH1 and IDH2 genes was performed with either the AmpliSeq for Illumina Cancer Hotspot Panel v2 (Illumina, San Diego, CA, USA) or the AmpliSeq for Illumina Focus Panel (Illumina), respectively. Next generation sequencing was performed on an Illumina MiniSeq device following the manufacturer’s protocol [ 26 , 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent survey showed that around 3.2 cases per 1 lakh of population per year suffering from GBM and also showed a remarkably poor prognosis with only 26-33 % survival rate in 2 years and around 5 % survival in 5 years. [1][2][3][4][5][6][7][8][9][10][11][12] A significant progress has been made in making drugs for brain cancer or similar cancer through radiation therapy, resection techniques and chemotherapy but the survival of the median patient is significantly lower. [9,17] This short survival rate under modern medication forces us to further study the process of Glioblastoma Malignant with a better understanding.…”
Section: Introductionmentioning
confidence: 99%